Xanthine oxidase inhibitory activity of Arcangelisia flava - Fatmawati; Subandrate; Safyudin; Medina Athiah; M Fitra Romadhon; Aulia Firdha Tariza (Acta Biochimica Indonesiana)
Background: Hyperuricemia is characterized by elevated levels of uric acid in the blood, produced from its precursor's xanthine and hypoxanthine via xanthine oxidase. Arcangelisia flava, an herbal medicine containing flavonoids, may decrease uric acid levels by inhibiting the xanthine oxidase.